The Effect of Islamic Work Ethics and Affective Commitment on Quality of Work Life and Turnover Intention of Sharia Bank - Viona Anin Dwita; Rozikan (Universitas Muhammadiyah Yogyakarta, 2022)
Maintaining the good performance of an employee must continue to be carried out by the company. This can be done by controlling the quality of work life and intention to leave, both of which are considered to be influenced by Islamic work ethics and affective commitment. Therefore, this study examined the effect of Islamic work ethic and affective commitment on the quality of work life and intention to leave. The object of this research is Bank BPD DIY Syariah. In this quantitative study, data were collected using a questionnaire distributed to employees of Bank BPD DIY Syariah. The questionnaires used in this study were 55 questionnaires that were analyzed using the SmartPLS 3.0 application. The test results show the positive influence of Islamic work ethic and affective commitment on the quality of work life. It was also found that the negative effect of Islamic work ethic on the intention to leave, while affective commitment had no effect on the intention to leave. Employees with Islamic work ethics and affective commitment show attitudes encouraging them to do their best. Employees focus on self-achievement, the relationship between employees and the company’s achievements. For this reason, bank management is expected to take several steps in order to improve Islamic work ethics and affective commitment to employees, such as incorporating Islamic work ethic values ​​in corporate culture and paying more attention to the needs and desires of employees.